Effects Of A Lactobacilli Probiotic On Survival And Mobility Of Female Drosophila Melanogaster With Alzheimer’s Disease - Ting Lim, Hui (Pusat Pengajian Teknologi Industri, 2020)
Alzheimer's disease (AD), as the most prevalent form of aging-associated neurodegenerative disease, progressed in an irreversible manner while approaching epidemic proportions with no cure or preventative therapy yet available. The probiotic strain Lactobacillus fermentum DR9 has been reported for exhibiting anti-aging effects on lifespan and muscle in senescence-induced rats, with AD-reversal potential by alleviating neurodegeneration in the eye of AD-induced Drosophila. Using an inducible Drosophila AD model by human Aβ42 expression with UAS/GAL4 system, the study was carried out to evaluate the effects of probiotic administration on the survival and mobility of female Drosophila melanogaster with AD. Evaluated by survival assay, the administration of L. fermentum DR9 for 24 days improved survival by increasing the survival percentage of female D. melanogaster AD model, as compared to the untreated control.